Manajemen Layanan Khusus Antar Jemput Siswa Kelompok Bermain An Najah Tanggul - Meylini Triya Novitasari; Asri Widiatsih; Pipit Rika Wijaya (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2025)
The student shuttle services are a critical component of special service management in early childhood education, especially in institutions serving underprivileged communities. This study aims to explore the planning, implementation, and evaluation of the shuttle service at KB An Najah, an Islamic early childhood institution under a foundation that offers free education to orphans and underprivileged children in Tanggul District, East Java. Using a descriptive qualitative approach through interviews, observation, and documentation, the findings reveal that the service emerged from parents’ time constraints and safety concerns, with 12.96% of students relying on it daily. Despite its benefits, the service operates informally without written SOPs, limited personnel, and unstructured coordination. Nonetheless, it significantly supports student attendance and parental peace of mind. This study highlights the need for more structured and sustainable service management practices in community-based educational settings.